The cost of high suicide rates in Japan and the Republic of Korea: Reduced life expectancies - United Nations (Asia-Pacific Population Journal, 2017)
Japan and the Republic of Korea, while having some of the highest life expectancies in the world, also have the highest suicide rates. This study uses actuarial multiple decrement techniques to calculate the reduction in life expectancy due to suicide in these countries. As of 2013, suicides shortened life expectancy at birth by 1.12 per cent in Japan and 0.83 per cent in the Republic of Korea. Most critically affected by suicide are Japanese males, with a 1.50 per cent reduction in life expectancy at birth. Additionally, the Republic of Korea sees a 0.80 per cent reduction in life expectancy at age 60 – a disturbingly high percentage when considering the high mortality rates from natural causes of death at this age. These results suggest that high suicide rates in Japan and the Republic of Korea have massive implications in terms of social costs and economic productivity.